Macrofungi from Castanea sativa Mill. and Quercus pyrenaica Wild.: Evaluation of mycorrhizal vs nonmycorrhizal fungi biodiversity – Project AGRO 689 - Baptista, Paula (2011)
The present work concerns results from the Project AGRO 689 on evaluation of macrofungi biodiversity associated with chestnut and oak trees in the northeast of Portugal (Trás-os-Montes), a region where these species have important social and economical roles. The study of relative abundance of mycorrhizal and nonmycorrhizal species and of edible vs non edible mushrooms are also main goals of this work. Ecological and economical impacts of edible fungi harvesting, including the impact on mycorrhizal and nonmycorrhizal species, are also under evaluation. Field work took place from October 2004 to December 2005. Total macrofungi were collected weekly during autumn and spring and monthly during the rest of the year, in five plots of 100m2 each per habitat. Identification and quantification of carpophores were made. Along the two years, 17 species belonging to 11 genera were collected in chestnut tree habitat. The distribution of species by functional groups shows a dominance of mycorrhizal species (59%). During the same period, oak tree habitat showed 59 species belonging to 27 genera. In contrast with chestnut tree habitat, the distribution by functional groups in oak habitat showed a slight dominance of saprotrophic species (49%). The reduced macrofungi biodiversity here shown will be discussed taking into account the particular climatic conditions in the northeast of Portugal during the main growing seasons of the current study.